Impact of the intensive psychological intervention care on post-traumatic stress disorder and negative emotions of teenage female patients seeking an induced abortion - Liu, Huiling; Wu, Fengdi; Liao, Guixia; Mai, Sizi; Ouyang, Meijin (Frontiers in Psychiatry, 2023)
Aim This study aimed to investigate the effects of intensive psychological intervention care on adverse emotions and post-traumatic stress disorder (PTSD) symptoms in female teenage patients after induced abortion. Methods This prospective cohort study included 100 teenage female patients seeking induced abortion who were randomly divided into two groups: the intervention group (n=50) and the control group (n=50). The intervention group received intensive psychological intervention care, while the control group received standard routine nursing. The scores of the PTSD checklist for DSM-5 (PCL-5), self-rating depression (SDS), and self-rating anxiety scale (SAS) were compared between the two groups at 1 month and 3 months after the operation. Results The intervention group had lower risk of developing PTSD (24% vs 44%), depression (10% vs 32%), and anxiety (0% vs 12%) symptoms at 1 month after the surgery. However, there were no significant differences observed between the two groups at 3 months after the surgery. Furthermore, the intervention group had significantly lower scores in PCL-5 (27.4±5.4 vs 31.8±5.7; 20.5±7.1 vs 25.0±7.5; P <0.05), SDS (31.8±5.4 vs 37.8±6.6; 26.8±5.0 vs 31.4±7.2; P <0.05), and SAS (32.7±5.0 vs 39.8±6.9; 25.0±2.7 vs 27.5±2.8; P <0.05) at 1 month and 3 months after induced abortion. Conclusion These findings suggest that intensive psychological intervention care can reduce the incidence and severity of depression, anxiety, and PTSD symptoms in teenage patients who undergo induced abortion.